1994
DOI: 10.1148/radiology.192.1.8208948
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional US of the fetus. Work in progress.

Abstract: The technique has the potential for recording complete anatomic studies for review and visualization of detail that is difficult to perceive on conventional US scans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 0 publications
2
10
1
1
Order By: Relevance
“…macroscopic fetal structures seen at autopsy are clearly depicted. The 3D image quality obtained from this study and our previous fetal cardiac study [14] is much higher than that obtained from 3D ultrasound studies on live fetuses [16][17][18][19]. This is due to the absence of motion artefact caused by fetal and maternal movement and cardiac pulsation and blood flow, apart from the higher intrinsic tissue contrast of the imaging modality.…”
Section: Discussioncontrasting
confidence: 55%
“…macroscopic fetal structures seen at autopsy are clearly depicted. The 3D image quality obtained from this study and our previous fetal cardiac study [14] is much higher than that obtained from 3D ultrasound studies on live fetuses [16][17][18][19]. This is due to the absence of motion artefact caused by fetal and maternal movement and cardiac pulsation and blood flow, apart from the higher intrinsic tissue contrast of the imaging modality.…”
Section: Discussioncontrasting
confidence: 55%
“…Another study by Merz et al 17 showed that just adding the simple 3D orthogonal image provided a diagnostic gain of 46.2%, and the combined 3D display provided a diagnostic gain of 71.5%. Kelly et al 18 concluded that 3D ultrasonography of the fetus allows complete anatomic study and visualization of detail that is difficult to perceive on conventional 2D scans.…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of this study we've focused primarily on a data flow in a typical obstetrics US scan, performed in B-Mode, with spatial resolution of 256×256, maintaining a contrast resolution of 8 bits (256 shades of gray). In such a study, the raw data required for the reconstruction is acquired by driving the transducer in a rectilinear, uniform direction with constant speed [13], [14]. The number of slices acquired depends on the specific application.…”
Section: Resultsmentioning
confidence: 99%